Five-year survival and causes of death in patients on home parenteral nutrition for severe chronic and benign intestinal failure. Issue 4 (August 2018) - Joly, Francisca; Baxter, Janet; Staun, Michael; Kelly, Darlene G.; Hwa, Yi Lisa; Corcos, Olivier; De Francesco, Antonella; Agostini, Federica; Klek, Stanislaw; Santarpia, Lidia; Contaldo, Franco; Jonker, Cora; et al.
Summary: Background & aim: Home parenteral nutrition (HPN) is the primary treatment for chronic intestinal failure (IF). Intestinal transplantation (ITx) is indicated when there is an increased risk of death due to HPN complications or to the underlying disease. Age, pathophysiologic conditions and underlying disease are known predictors of HPN dependency and overall survival. Although the cause of death on HPN is mostly related to underlying disease in these patients, the relationship between mortality and duration of HPN use remains unclear. The purpose of the present study is to describe factors associated with survival and HPN dependency as well as causes of death in adult patients requiring HPN for chronic intestinal failure during the first 5 years of treatment with HPN. Methods: A multicenter international (European and USA) questionnaire-based retrospective follow-up of a cohort of 472 IF patients who started HPN was conducted between June and December 2000. Study endpoint was either end of 5-year follow-up, weaned-off HPN, ITx, or death on HPN. Data were analyzed for HPN dependence and overall survival using Kaplan–Meier models and log rank tests. Results: The overall survival probability was 88%, 74% and 64% at 1, 3 and 5 years respectively. Survival was inversely related to age (p < .001) and higher in patients with Crohn's disease or chronic idiopathic pseudo-obstruction. A total of 169 (36.5%) patients were weaned-off HPN mainly (80%) within the first year and most frequently in patients with fistulae. Five of the 14 patients who underwent ITx died. By the end of the study, 104 (23%) of patients died on HPN; 65% of deaths occurred within the first 2.5 years of HPN. Conclusions: Younger ages at HPN initiation and underlying pathologies are significantly predictive of survival on HPN. Risk of death is greatest during the first 2 years of HPN.